4-[(3,4-Dimethoxybenzylidene)amino]-1,5-dimethyl-2-phenyl-1H-pyrazol-3 (2H)-one - Asiri, A.M.; Khan, S.A.; Tan, K.W.; Ng, S.W. (International Union of Crystallography, 2010)
The imino-carbon double-bond in the title Schiff base, C(20)H(21)N(3)O(3), has an E configuration; the six-membered aromatic substituent (r.m.s. deviation = 0.012 angstrom) is nearly coplanar with five-membered pyrazole substituent (r.m.s. deviation = 0.031 angstrom), the dihedral angle between the two systems being 11.4 (1)degrees]. The phenyl ring connected to the pyrazole ring is aligned at 45.5 (1)degrees with respect to this five-membered ring. The N atoms in the ring show pyramidal coordinations.